Análise da influência de parâmetros acústicos na inteligibilidade da fala: um estudo em salas de aula de escolas municipais de João Pessoa. - Santos, Roberta de Lourdes Silva dos (2012)
Researchs in the area of environmental comfort conducted in schools reported that, considering the thermophysical variables, the acoustic variable is more important than the other variables, especially in relation to thermal, luminous and indoor air quality variables, since this is the variable that is directly tied to speech intelligibility, with impacts on the performance of teachers and students. However, the sound pressure level of speech, the reverberation of the room and the background noise are factors that can affect the speech intelligibility in classrooms. Thus, from the guidelines of Brazilian and international standards, we evaluated the acoustic conditions of 119 classrooms of municipal schools in the city of Joao Pessoa, Brazil. Through the construction of a beta regression model, it was verified how much the acoustic parameters of these rooms can affect the speech intelligibility of teachers. It was found that the level from external sources to classrooms, background noise, reverberation time and the speech intelligibility index is not within the reference values established in those standards. The mathematical modeling showed a high consistency, with a value of 0,9956 for the pseudo R2 and the variable "Reverberation Time" (p-value = 2 . 10-16) was the most representative, odds ratio= 0,228126, demonstrating that this variable affects the quality of intelligibility at around 77,18%.